2015
DOI: 10.1016/j.marpetgeo.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

3D modelling of the Sorbas Basin (Spain): New constraints on the Messinian Erosional Surface morphology

Abstract: a b s t r a c tThe scenario of the Messinian Salinity Crisis (MSC) remains one of the most debated topics in the Mediterranean realm and especially in the Sorbas Basin, which is one of the type-localities of MSCrelated deposits. After a recently improved chronostratigraphic framework of the Miocene and Pliocene deposits of the basin, this work is an attempt to image the morphology of the Messinian Erosional Surface (MES) at depth. We built a basin-scale 3D-model of the Miocene and Pliocene series that confirms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…For this reason, the Zorreras Mb. has been usually considered (with some notable exceptions, see Braga et al, 2006, Clauzon et al, 2015Do Couto et al, 2015) a time equivalent of the uppermost Messinian Lago-Mare deposits observed elsewhere in the Mediterranean, just below the return to fully marine condition at the Miocene/Pliocene boundary Rouchy & Caruso, 2006). Along the basin margins, and particularly along the northern one, the alluvial plain deposits interfinger with thick-bedded, sheet-like, and/or channelized conglomerates representing alluvial fan systems (Moras Mb. of Mather et al, 2001); in these proximal areas, two lacustrine white limestone horizons allow the correlation with the depocentral succession.…”
Section: Loxoconcha Djaffarovi) and Molluscs (Limnocardinae Bivalves)mentioning
confidence: 99%
“…For this reason, the Zorreras Mb. has been usually considered (with some notable exceptions, see Braga et al, 2006, Clauzon et al, 2015Do Couto et al, 2015) a time equivalent of the uppermost Messinian Lago-Mare deposits observed elsewhere in the Mediterranean, just below the return to fully marine condition at the Miocene/Pliocene boundary Rouchy & Caruso, 2006). Along the basin margins, and particularly along the northern one, the alluvial plain deposits interfinger with thick-bedded, sheet-like, and/or channelized conglomerates representing alluvial fan systems (Moras Mb. of Mather et al, 2001); in these proximal areas, two lacustrine white limestone horizons allow the correlation with the depocentral succession.…”
Section: Loxoconcha Djaffarovi) and Molluscs (Limnocardinae Bivalves)mentioning
confidence: 99%
“…However, existing depth estimates for the entire Abad Member range from 200 to 1000 m [Dronkert, 1976;Troelstra et al, 1980;Riding et al, 1998;Poisson et al, 1999;Baggley, 2000], indicating a need for better constraints on paleobathymetry. Coeval fringing carbonate reefs [Martín and Braga, 1994;Braga and Martin, 1996] are used to constrain the basin's horizontal dimensions to~40 × 30 km 2 (Figure 1b) (see geological maps of Krijgsman et al [2001] and Do Couto et al [2014]).…”
Section: Sedimentology and Chronologymentioning
confidence: 99%
“…This software is able to interpolate a surface based on external (outcropping geological interfaces, orientations) and internal data (well tops, depth migrated seismic images) using a cokriging method Guillen et al, 2008). During the modeling process, the sequence of interpolation of geological units is given by a synthetic geologic pile that accounts for the nature of the contacts separating geological units: "erosive" in the case of an unconformity or "onlap" in the case of a sedimentary filling, for instance (for details, see Do Couto et al, 2015). In the present case, the MES is constrained as an erosive surface.…”
Section: Three-dimensional Reconstructionmentioning
confidence: 99%